Decreased tracking, increased earning: Evidence from the comprehensive Polish educational reform of 1999 - Luca Flóra Drucker; Dániel Horn (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2016)
The Polish educational reform in 1999 is often considered successful as the results of the Polish students, and especially that of the low-performers, on the OECD PISA tests have improved significantly since the introduction of the new system. The reform extended the previous 8-year undivided comprehensive education to 9 years, core curricula were introduced and the examination, admission and assessment systems were changed. It has been argued before that this longer comprehensive education improved the test performance of worse performing students; hence increasing average performance and decreasing inter-school variation of test scores. However, the lack of reliable impact assessment on long-run labour market effects of this reform is awaiting. In this paper, we aim to fill this gap by looking at the causal effects of the reform. By comparing the labour market outcomes of the pre- and post-reform cohorts, we find a non-negligible and positive effect. We look at employment and wages as outcomes. Using data from the EU-Statistics on Income and Living conditions, and pooling the waves between 2005 and 2013 and taking the 20-27 year-olds, we generate a quasi-panel of observations to estimate the treatment effect by difference-in-difference estimation. We find evidence that the reform was successful on the long-run: the post-reform group is more likely to be employed and they also earn higher wages. On average, the treatment group is around 2-3% more likely to be employed, which effect is driven by the lowest educated. The post-reform cohort also earns more: we find an over 3% difference in real wages, which is also more pronounced for the lowest educated.
Keywords: I21; I24; I26; J24; 330; education reform; Poland; detracking; labor market; difference-in-difference